Pelatihan dan Pendampingan Pembuatan Telor Asin dari Telor Ayam sebagai Usaha Peningkatan Kreativitas dan Inovasi Produk Unggulan - Ni Komang Sumadi; I Gede Aryana Mahayasa; Ni Nyoman Adityarini Abiyoga Vena Swara; I Wayan Suartina; Putu Cita Ayu (JURNAL SEWAKA BHAKTI, 2021)
Jatiluwih Village has long been known by tourists, both foreign and domestic as one of the tourist destinations in Tabanan district. The natural scenery in the form of terraced terraces offered to tourists has been recognized worldwide and has become one of UNESCO's protected cultural heritage. To support the economy, Jatiluwih village is also known as a center for rice barn and broiler breeding. The product of purebred chicken eggs produced in Jatiluwih village is one of the largest in the Penebel district. So far, the production of purebred chicken eggs has been used to meet the people's need for eggs and sold to markets. The training and mentoring provided for community service aim to invite people to increase creativity and innovate with chicken egg products produced by making salted eggs. These training and mentoring activities include training on making salted eggs from chicken eggs, demonstrations and practice of making salted eggs, tips on branding the salted eggs produced, and assistance in marketing the products. The benefits that can be obtained from this training and mentoring are the creation of other types of superior products from Jatiluwih village, namely salted eggs from chicken eggs and being able to increase the income of the Jatiluwih village community. The strategic target of this training and mentoring activity is PKK Jatiluwih village women with 20 participants. The expected output is the creation of salted egg products from chicken eggs which will become one of the superior products of Jatiluwih village, Penebel District, Tabanan.